What do we know about birds' use of plant volatile cues in tritrophic interactions? - Mrazova, Anna; Sam, Katerina; Amo, Luisa (Current opinion in insect science, 2019)
The first study showing that birds can smell herbivore-induced plant volatiles was published ten years ago. Since then, only 12 studies have been published, showing contradictory results. This review evaluates the role of birds in relation to the crying for help hypothesis and their use of olfactory cues. In accordance with the methodologies used in previous studies, we herein provide a summary of experimental approaches and describe the advantages and disadvantages of experiments conducted in nature versus aviaries. Moreover, we recommend experimental methodologies which lead to a deeper knowledge of the topic, including reflection on the induction of plant defenses and adaptations of birds. Finally, we propose some interesting questions for future research to direct further studies towards a thorough and accurate description of birds' roles in tritrophic interactions.
Keywords: Plants; Insecta; Smell; Cues; podněty; potravní řetězec; čich; Herbivory; Animals; ptáci; hmyz; Birds; těkavé organické sloučeniny; Volatile Organic Compounds; zvířata; rostliny; Food Chain; býložravci